Kolos rodyjski: gdzie stał i jak był wykonany - Wujewski, Tomasz (Artium Quaestiones, 2019)
Colossus of Rhodes: Where It Stood and How It Was Made The author, just as Ursula Vedder, who has expressed the same opinion recently, has been long sure that the place where the Colossus of Rhodes was located was the acropolis of the town of Rhodes. The paper includes also some arguments that have not been presented by the German scholar. At first, some source information concerning the Colossus has been briefly summarized. For instance, the expression in APV, 171 (Overbeck 1543), ou gar hyper pelagos monon anthesan alla kai en ga, may be understood as confirming its location in the acropolis: “it stood not only close to the sea, but also on the earth.” In fact, there it would have loomed over the land and the sea, and, as big as it was, it could be seen from a distance. The text by Philo of Byzantium is not credible, as it was written quite late. Then the problem has been analyzed critically. As regards the legend of Colossus bestriding the entrance to the harbor, one may add to the already listed counterarguments that for static reasons a piece of sculpture shaped that way would have needed a third footing attached to the sea bottom at the harbor entrance, which would have made the ships’ access to the harbor difficult. Besides, such a pose of a god would have seemed a little indecent. A hypothesis that situates the Colossus at the end of a pier in the Mandraki Bay, preferred by many scholars, also has its weak points. Placed there, the construction site would have been too small, particularly that construction took at least twelve years, and it would have been difficult to move building materials along the narrow and long pier which under such circumstances could not be used as part of the harbor. According to Strabo (XIV, 2, 5) the harbor was accessible only to authorized personnel. Was it then a good location for a work of art intended to glorify the people of Rhodes? Even if the Colossus had been accessible there, it would have been visible only in a shortened perspective, in frog’s eye view. Still, the most important was the problem of proper display of the statue. Placed on the pier, it would have to turn its back either to the town, or to the sea, and in both cases connotations would have been unwelcome. Such details were essential for ancient Greeks. For static and constructional reasons, one must also reject a hypothesis that the Colossus put his palm over the eyes, as if examining the horizon. If it is true that the relics of the statue remained for several hundred years intact, they would have blocked access to the harbor since most probably they would have fallen into the sea. Besides, would the iron elements have resisted corrosion well enough to be recognizable? Placed on the pier, the Colossus would have been invisible to the crews of ships approaching the town from the west and the same would have been true had it been situated at the present location of the palace of the Great Masters of the Knights Hospitaller. The placement of the statue in the sanctuary of Helios at the present corner of Sofouli and Khimaras streets is also improbable, since the area is really small and the Colossus would not have made a prominent component of the town skyline. Hence, the acropolis must have been the most convenient place, just as in other Greek towns, particularly in Athens where it was the site of the city patron’s worship. Some scholars argue that the temple in the acropolis was dedicated to Apollo, but when the Colossus was constructed Apollo was commonly identified with Helios who was the most important patron of the island. The statue, with his face turned to the east – the town and the sea – might have stood near that temple (ill. 1-2), towering over it. From the west, the steep rock of the acropolis practically made it impossible to watch the Colossus from the western shore, while from the sea it was visible only as a silhouette, an orientation point for the approaching ships (ill. 3), particularly if it was gilded like the statue of Athena Promachos in Athens. This can actually be the origin of the legend that the Colossus of Rhodes was also a lighthouse. Situated in the acropolis, the statue would have been visible both from the town and the sea on both sides of the island. If the damaged Colossus remained intact for centuries, it was because removing it from the acropolis was much more difficult than removing from the wharf. The noun “colossus” originally meant “something towering” (cf. Colossae and Colophon, towns upon hills). The other part of the paper focuses on the technology of construction. Some scholars were too eager to draw from Philo’s description conclusions about the Colossus’ structure and the building methods applied. If the statue had stood at the end of the pier, most likely it would not have been hilled up since the area was too small. Due to the pressure of dirt, boarding such an embankment (A. Gabriel’s claim) would have required 40-45 meter long struts for which there was no room. Moreover, with each subsequent raising of the embankment the struts would have to be multiplied and made much longer, which would have been both costly and technologically challenging. With each new layer of dirt, founding furnaces would have to be removed (as, according to Gabriel, they were located on the embankment) and then put back. A high embankment would have required the use of gigantic ladders, unstable and dangerous. What is more, it would have made it impossible to control the form of the work in progress. All that would have been irrational, while ancient Greeks do not really deserve such a charge. In the author’s opinion, the Colossus was erected within a wooden scaffolding. Founding particular elements of the statue on site was rather unlikely. An external dirt coat would not have helped since there was no clay core inside it, which would have made the alloy’s cooling speed radically unequal. Partial casting is also unlikely as it would have required a 1:1 model (30-35 meters high). Had the model been smaller, errors in calculating detailed measurements would have been inevitable. The author believes that the Colossus of Rhodes was made of hammered bronze sheets riveted to the inner metal skeleton. Such a technique made vertical transportation easier and allowed the constructors to correct the process of montage by bending the sheets whenever necessary. It cannot be excluded that the heads of the rivets and lines of contact between the sheets were masked with solders that did not require much alloy, although in higher sections of the statue the wind would have cooled it quite rapidly. The noun “colossus” did not originally imply a gigantic size but only a slightly archaic look of the sculpture so that the Colossus of Rhodes might have been somewhat similar to very ancient and artistically primitive stiff statues of Helios. On the other hand, it might have alluded to the mythic Telchins who were the first to make statues of gods. (For static reasons, contrapposto was out of the question in the statues of that size, besides it would have been impossible to fill its interior with stones.) Another aspect of making the Colossus look archaic was the use of a modified technique of sphyrelaton. In the author’s opinion, the base of the statue and maybe its higher parts as well, up to the level of ankles, contained carefully sized and braced blocks of stone. They were drilled through to hold the lower ends of the metal internal skeleton made according to the schema of a spatial grid, perhaps used on that occasion for the first time in history. Such a fixture protected the Colossus from the wind pressure so effectively that it remained standing for dozens of years, being vulnerable to earthquakes. The fallen Colossus must have looked like a debris of rods and tin, while the stones from the fixture could be seen in the “abyss” (Plinius), below the level of the ankles, where the structure was actually bent (it must have been bent there rather than at the level of the knees, since looking inside the ruin was easy: the ankles were situated about two meters above the base.) The third footing point might have been camouflaged with some attribute (a spear or a torch). It cannot be excluded that originally Chares had been planning a statue half the final size, similar to the previously known colossal pieces of sculpture, but the pride of the people of Rhodes, emulating Athenians, made them want a Colossus twice as big (Sextus Empiricus, pros mathem., VII, 107 n.). Making the statue look archaic and using an old technology plus some innovations allowed Chares to make their extravagant wish come true. The archaic look might have been achieved thanks to a reference to some old statue of Helios, which perhaps could be found in the neighboring temple. The torso might have been topped with the head, cast separately, although the trouble with placing it so high makes one doubt it.